Effect of Application of Botanical Pesticida xtracts of Citrus (Citrus aurantifolia) and Betel (Piper betle) Leaves on the Mortality of the Pest (Plutella xylostella) on Jengkol (Phitecellobium jiringa) plants - Mardhiansyah, Muhammad; Cahyani, Putri; Pebriandi, Pebriandi; Irfani, Ewi; Lestari, Ika; Masruri, Niskan Walid (JURNAL ILMU-ILMU KEHUTANAN, 2024)
Plutella xylostella are one of the pests that attack BPDASHL (Watershed Management Agency and Protected Forest) nurseries in Pekanbaru. One of the plant seedlings attacked by this pest is the Phitecellobium jiringa. Pest control efforts that have a positive impact are botanical pesticides. This study aims to determine the best concentration of a mixture of Citrus aurantifolia leaf extract and Piper betle leaf against hanging Plutella xylostella pests on Phitecellobium jiringa plants. This study used a completely randomized design (CRD), with the treatments namely: P1 = a mixture of C. aurantifolia leaf extract and P. betle leaf 50 g/L, P2 = a mixture of C. aurantifolia leaf extract and P. betle leaf 100 g/L, P3 = a mixture of C. aurantifolialeaf extract and P. betle leaf 150 g/L, and P4 = a mixture of C. aurantifolia leaf extract and P. betle leaf 200 g/L. The observation variables in this study were temperature and humidity, the initial time of death, lethal time50 (LT50), daily mortality, and total mortality. The results showed that the application of botanical pesticide extract of C. aurantifolia leaf and P. betle leaf was efficient on the mortality of hanging P. xylostella pests with a total mortality result of 100%. The best the best concentration is a mixture of C. aurantifolia leaf extract and P. betle leaf 200 g/L (P4).